A Preliminary Study Investigating Maternal Neurocognitive Mechanisms Underlying a Child-Supportive Parenting Intervention - Giuliani, Nicole R.; Beauchamp, Kathryn G.; Noll, Laura K.; Fisher, Philip A. (Frontiers in Behavioral Neuroscience, 2019)
Although interventions that promote child-supportive parenting for children have been shown to positively impact caregiving behaviors as well as child behavioral and neurobiological functioning, less is known about which aspects of maternal brain functioning are affected by such interventions. In the present study, we conducted a preliminary evaluation of the impact of the Filming Interactions to Nurture Development (FIND) video coaching program on mothers with at least one child age four or younger. We employed a waitlist control design with pre-post data. Compared to mothers in the control condition (n = 16), mothers who received FIND (n = 16) showed changes in neural measures of inhibitory control and behavioral measures of parenting self-evaluation during a series of functional neuroimaging tasks. Specifically, we found a group by time interaction in clusters in the left inferior frontal gyrus and insula for the Correct Stop > Correct Go contrast of the Stop Signal Task, where FIND increased brain activity associated with inhibitory control compared to mothers in the control condition; and FIND increased mothers’ endorsement of child-supportive parenting traits in the Parenting Self-Evaluation Task. Exploratory moderators, study limitations, and the implications of these findings for strength-based parenting programs are discussed.